SEJARAH PERS ISLAM DI PALEMBANG (1965-1972): Studi atas Surat Kabar Mingguan “Nusa Putera” - Ottoman M.Hum (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
The press is an institution of mass communication that could serve the interests of the information society. Everyday the press provides an overview of a variety of events, providing a place for the community to issue a written opinion and pass on societal values from generation to generation. In the face of changes take place rapidly in communities clearly such information is very helpful. Weekly Newspaper "Mimbar Masjarakat" and "Nusa Putera" edition of South Sumatra (1965 AD-1972 AD), is a testament to the history of the Islamic press in Palembang, where the existence and history are not so known to the public and public audiences in this city. Lunge and press struggle in build, develop, prosper, and educating the people of Palembang through its role is so urgent and complex. This constitutes an irony of history for Islam in the Indonesian press in general and in the city of Palembang in particular. This paper reveals the history and role and contribution of "Mimbar Masjarakat" and "Nusa Putera" Edition South Sumatra is very significant social change in Palembang. Keywords: -Islamic Press, -Nusa Putera, -Palembang